Genomic features and pathogenic potential of Streptococcus agalactiae isolated from bovine clinical mastitis. (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The goal of this study is to describe the genome of Streptococcus agalactiae that was found in clinical mastitis in cattle in Bangladesh. This work will show how strong the bacteria are and how important they are for public health. Materials and Methods: Whole genome sequencing (WGS) was performed using the Illumina MiSeq platform, followed by comprehensive analysis with various bioinformatic tools to identify key genomic features. Results: WGS revealed that the isolates are closely related, belonging to sequence type ST4, a rare type previously identified in both human and animal hosts. The isolates possess 44 virulence-related genes linked to adherence, capsule biogenesis, enzyme production, immunoreactive antigens, protease, and cytolysin production. They also carry two pilus islands (PIs), PI-1 and PI-2b, which are often associated with invasive diseases. PI-2b proteins are key targets for vaccine development against Group B Streptococcus (GBS). The isolates belong to serotype Ia and carry the gbs2018-2 variant, indicating their adaptability to a wide range of hosts, including humans and animals. These virulence factors are critical for understanding S. agalactiae’s pathogenicity and developing vaccines against its infections. Additionally, the isolates harbor antimicrobial resistance genes conferring resistance to glycopeptides (vanT, vanY), macrolides (mreA), peptides (mprF), penicillins and β-lactams (pbp), and aminoglycosides. Source tracking via the BacWGSTdb website identified these isolates as closely related to human pathogens, indicating their zoonotic potential. Conclusion: These results suggest that S. agalactiae could be a zoonotic pathogen. This highlights the need for ongoing genomic surveillance to fully understand how it causes disease and come up with effective ways to control it.J. Adv. Vet. Anim. Res., 12(1): 80–89, March 2025http://doi.org/10.5455/javar.2025.l874